If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7y = 20 + -4x Solving 6x + -7y = 20 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6x + 4x + -7y = 20 + -4x + 4x Combine like terms: 6x + 4x = 10x 10x + -7y = 20 + -4x + 4x Combine like terms: -4x + 4x = 0 10x + -7y = 20 + 0 10x + -7y = 20 Add '7y' to each side of the equation. 10x + -7y + 7y = 20 + 7y Combine like terms: -7y + 7y = 0 10x + 0 = 20 + 7y 10x = 20 + 7y Divide each side by '10'. x = 2 + 0.7y Simplifying x = 2 + 0.7y
| x+14y=6 | | 1/4=0.25 | | 7n-10-9n=13 | | v^2+8=30 | | y=-0.5(1)+4 | | 2(6-14y)+14y=2 | | -10a^2+3a+2=0 | | 3n^2-8n-3=0 | | 6x=60-6x | | 25m^2-16n^2=0 | | .12-56=-44 | | 27x+4=17x-36 | | 6x-7y=20 | | x^2+2=20 | | y=-0.5(0)+4 | | 5-4(x+6)+5x= | | 2(s+3)+6(s-4)+1= | | -3(7n-2)=-99 | | 36a^2=16 | | 5(x-3)-4(x-3)= | | (8x^4)-125x=0 | | 12-(n+3)=10 | | 12x-(6-3x)= | | 12x-(6-3)= | | 5((2)+y)=20+3(2) | | n^2+5=21 | | 5-5z+7+z= | | x+1=21 | | 9x^2+18x+9=0 | | 2x=15y | | 7(1-7v)+3=108 | | -2((2)+3y)=18 |